Present and future advanced laparoscopic surgery. Issue 2 (22nd April 2013) - Rivas, Homero; Díaz‐Calderón, Daniela
Abstract Modern laparoscopy, starting with Kurt Semm's insufflators and the first successful appendectomies, has only been around for approximately 30 years. Since those early successes, the technology has grown from the inception of basic laparoscopy to endoscopic surgery through natural orifices, and it continues to evolve by leaps and bounds with computer‐assisted surgery and improved robotics in surgery. Without question, laparoscopy has revolutionized the way we perform standard surgery, especially relative to the techniques that had been used for hundreds of years. Despite the development of multiple novel technologies since the 1980s, very little has changed with regard to basic conceptualizations and practice of laparoscopy. In this review article, we will describe the highlights of recent advanced laparoscopic surgery procedures, their potential applications within the field of surgery, and how these advances may impact and improve future quality and patient outcomes.